(untitled) (Хабаршы. Психология және социология сериясы, 2022)
This article attempts to analyze an extreme form of isolation of a certain group of people, the cases of their social isolation and self-isolation during complete or complete detachment from the society. The COVID-19 coronavirus pandemic, which has affected the material and spiritual social lives of many people around the world, is the subject of recent sociological research. When people’s lives revolve around Internet and online communication, the use of smartphones leads to a decrease in emotionality and eliminates the need for personal interactions. Moreover it causes the strong feeling of isolation; disruption of social ties; degradation of consciousness.The article discusses the main types of social isolation by the initiator, that take place in these kinds of situations. The study also make an attempt to determine what kind of consequences can long and short-term isolation of people from each other lead to, the reasons for such a negative impact. The focus in this perspective is on isolated loneliness, which is defined as loneliness resulting from social disconnection as a result of forced social distancing and isolation during the COVID-19 pandemic. The article examines the role of digital technologies in the fight against loneliness in isolation during the pandemic. The authors conducted an online survey on the topic "Using digital technologies during social isolation" to determine the level of online use of services among the population of Taldykorgan. The number of respondents is 284. According to the results of this empirical study, the population is well adapted to digitalization and the time spent on the Internet is increasing. However the article also came to the conclusion that there is a growing demand for some types of activities, the impact of the quarantine situation. Many recognize that digitalization promotes transparency and is very effective, and have shown that information and communication technologies are able to unite people into a single system. Key words: social isolation, self-isolation, quarantine, pandemic, coronavirus, digitalization.